A Survey on Fauna of Ticks in West Azerbaijan Province, Iran - Z Telmadarraiy; A Bahrami; H Vatandoost (Tehran University of Medical Sciences, 2004)
Tick are considered as the main vector for transmission of various diseases to human being. This study was carried out to investigate the fauna of species belonging to two families of ticks, Ixodidae and Argasidae in west Azerbaijan province, Iran. A total number of 62 villages were selected randomly, from the study area 3278 ticks were collected with cluster sampling method, after collection they were identified by morphological characteristics using stereomicroscope device. The ticks were classified into seven genera and 15 species including following species: Concerning Ixodidae families, Rhipicephalus (42%), Hyalomma (41%), Boophilus (7%), Dermacentor (7%), and Haemaphysalis (3%). Genus Rhipicephalus, comprised R. bursa (73%), R. sanguineus (27%), had the highest prevalence in summer. The species of Hyalomma were H. asiaticum (27%), H. marginatum (25%), H. aegyptium (14%), H. dromedarii (13%), H. schulzei (12%) and H. detritum (9%). Their peak frequency occurred in autumn. The single species of genus Boophilus was B. annulatus. Its activity occurred in spring and summer seasons. In genus Dermacentor, D. marginatus (61%) and D. niveus (39%) were total species of this genus that had the highest prevalence in summer and autumn. In genus Haemaphisalis, H. sulcata (61%) and H. inermis (39%) were recorded as the main species. Their highest seasonal frequency occurred in summer. Among soft ticks only Argas persicus and Ornithodoros lahorensis were collected. A.persicus was active during the summer and winter during the nights and the second species was active during the spring and winter. In conclusion, it should be emphasized that prevalence of the families Argazidae and Ixodidae ticks were more evident in mountainous area in west Azerbaijan province.